Telemedicine and Telehealth in Urology—What Do the ‘Patients' Think About It? - Naik, Nithesh; Hameed, B. M. Zeeshan; Nayak, Sanjana Ganesh; Gera, Anshita; Nandyal, Shreyas Raghavan; Shetty, Dasharathraj K.; Shah, Milap; Ibrahim, Sufyan; Naik, Aniket; Kamath, Nagaraj; Mahdaviamiri, Delaram; D'costa, Kenisha Kevin; et al. (Frontiers in Surgery, 2022)
Telemedicine is the delivery of healthcare to patients who are not in the same location as the physician. The practice of telemedicine has a large number of advantages, including cost savings, low chances of nosocomial infection, and fewer hospital visits. Teleclinics have been reported to be successful in the post-surgery and post-cancer therapy follow-up, and in offering consulting services for urolithiasis patients. This review focuses on identifying the outcomes of the recent studies related to the usage of video consulting in urology centers for hematuria referrals and follow-up appointments for a variety of illnesses, including benign prostatic hyperplasia (BPH), kidney stone disease (KSD), and urinary tract infections (UTIs) and found that they are highly acceptable and satisfied. Certain medical disorders can cause embarrassment, social exclusion, and also poor self-esteem, all of which can negatively impair health-related quality-of-life. Telemedicine has proven beneficial in such patients and is a reliable, cost-effective patient-care tool, and it has been successfully implemented in various healthcare settings and specialties.